Effect of neoadjuvant chemotherapy on health-related quality of life in patients with muscle-invasive bladder cancer: results from JCOG0209, a randomized phase III study. (23rd July 2020) - Kitamura, Hiroshi; Hinotsu, Shiro; Tsukamoto, Taiji; Shibata, Taro; Mizusawa, Junki; Kobayashi, Takashi; Miyake, Makito; Nishiyama, Naotaka; Kojima, Takahiro; Nishiyama, Hiroyuki
Abstract: Background: Although neoadjuvant chemotherapy provides survival benefits in muscle-invasive bladder cancer, the impact of neoadjuvant chemotherapy on health-related quality of life has not been investigated by a randomized trial. The purpose of this study is to compare health-related quality of life in patients with muscle-invasive bladder cancer who received neoadjuvant chemotherapy followed by radical cystectomy or radical cystectomy alone based on patient-reported outcome data. Methods: Patients were randomized to receive two cycles of neoadjuvant methotrexate, doxorubicin, vinblastine, and cisplatin followed by radical cystectomy or radical cystectomy alone. Health-related quality of life was measured using the Functional Assessment of Cancer Therapy-Bladder (version 4) questionnaire before the protocol treatments, after neoadjuvant chemotherapy, after radical cystectomy and 1 year after registration. Results: A total of 99 patients were analysed. No statistically significant differences in postoperative health-related quality of life were found between the arms. In the neoadjuvant chemotherapy arm, the scores after neoadjuvant chemotherapy were significantly lower than the baseline scores in physical well-being, functional well-being, Functional Assessment of Cancer Therapy-General total, weight loss, diarrhoea, appetite, body appearance, embarrassment by ostomy appliance and total Functional Assessment of Cancer Therapy-Bladder. However, there was no difference in scores for these domains, except for embarrassment by ostomy appliance, between the two arms after radical cystectomy and 1 year after registration. Conclusions: Although health-related quality of life declined during neoadjuvant chemotherapy, no negative effect of neoadjuvant chemotherapy on health-related quality of life was apparent after radical cystectomy. These data support the view that neoadjuvant chemotherapy can be considered as a standard of care for patients with muscle-invasive bladder cancer regarding health-related quality of life. Abstract : UMIN Clinical Trials Registry Identifier: C000000093. Although health-related quality of life declined during neoadjuvant methotrexate, vinblastine, doxorubicin and cisplatin, its negative effect was not apparent on health-related quality of life after radical cystectomy and thereafter.